Estimation of the Demand function of Electrical Energy for the domestic sector in Duhok governorate and forecasting until year 2019 - ghazi, kovan Tamar; saleh, bahram Mahmood (Humanities Journal of University of Zakho, 2018)
Electricity is the most important source of energy and it has a vital in the daily functioning of contemporary societies, and is one the most important indicators in economic development, domestic sector in Dohuk suffers from a clear shortage of providing electricity, so the monthly demand and supply data for electricity is collected during the period 2013-2016. For the purpose of estimating demand for electricity and the gap between demand and supply. The paper has hypothesized that there are many variables that affect the demand electricity. These variables are: GDP, demand on effects of time delays in the electric power, temperature and population. The study aimed to estimate the demand for electricity in the household sector for the period 2013-2016 and forecasting demand for 2017-2019. To achieve the objective of the study and test its hypothesis, the descriptive approach has adopted, as well as the quantitative approach for estimating the function Demand and prediction. The results show that there is a significant relationship between independent variables and demand for electric power in the province of Dohuk.